The Role Of Organizational Development In Improving The Quality Of Training - Cahyani, Okik Dwi; Timan, Agus; Mutmainnah, Mutmainnah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Organisational development is an activity that continues to be carried out by all organisational settings. The purpose of organisational development is to improve the effectiveness of organisational performance. So that the quality of education can be maximised. This research method uses a literature review to conduct an in-depth study, which departs from the mini-observation at UNLA. The sources used in this literature review research are sourced from literature reviews using google scholar applications, mendeley and other online academic applications (Yandi et al., 2023). The findings of this study have two main themes, namely first, the role of organisational development in improving the quality of education is carried out through structural change, innovation in educational management, conducting human resource development and working with partnerships. Second, organisational development strategies in an effort to improve the quality of education are by adopting a data-based approach, promoting a culture of innovation and creativity, and making full use of information technology. There are still many shortcomings in this study, therefore further researchers are needed to further deepen this research.